Volume 3: Controls, Diagnostics and Instrumentation; Education; Electric Power; Microturbines and Small Turbomachinery; Solar B 2011
DOI: 10.1115/gt2011-46360
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Aerodynamic Radial and Axial Impeller Forces in a Turbocharger

Abstract: Aerodynamic forces are a major cause of turbocharger bearing friction. Thus, numerical simulations with ANSYS CFX are performed for a turbocharger turbine and compressor in order to determine these forces. Today, in common turbocharger CFD simulations the influence of the impeller backside cavity and blow-by are usually neglected. As a consequence, the axial forces on the impeller cannot be correctly determined. In this study therefore, the impeller backside cavity and blow-by were taken into account. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The variation range (max-min) assigned at the LE is greater (in percentage terms) and this is related to a third contribution factor, i.e., the axial thrust on rotor bearings. On this issue many authors investigated [13,14] and discussed that the thrust contribution from the leakage flow in the rotor backside cavity is usually greater than the momentum variation contribution due to blade flow deflection. The overall thrust tends to push the rotor toward the shroud at the LE resulting in a further reduction of the existing gap (while at the TE the axial thrust has no effect on the clearance).…”
Section: Input Uncertaintiesmentioning
confidence: 99%
“…The variation range (max-min) assigned at the LE is greater (in percentage terms) and this is related to a third contribution factor, i.e., the axial thrust on rotor bearings. On this issue many authors investigated [13,14] and discussed that the thrust contribution from the leakage flow in the rotor backside cavity is usually greater than the momentum variation contribution due to blade flow deflection. The overall thrust tends to push the rotor toward the shroud at the LE resulting in a further reduction of the existing gap (while at the TE the axial thrust has no effect on the clearance).…”
Section: Input Uncertaintiesmentioning
confidence: 99%
“…However, the total axial thrust predicted by the two methods was in good agreement with the experimental measurements. Raetz et al 18 analyzed the radial and axial forces on the impeller and concluded that the radial force on the impeller was much smaller than the axial force. Most of the aerodynamic parameters were evenly distributed in the circumferential direction, and the radial pressure gradient was mainly caused by the centrifugal force.…”
Section: Introductionmentioning
confidence: 99%
“…The backside cavity behind the rotor disk can affect the flow at rotor inlet and consequently turbine performance. The flow features within the cavity were investigated by Raetz et al [10] to calculate aerodynamic forces in a turbocharger. Results showed a flow structure with high total pressure gradients in the radial direction generated by centrifugal forces.…”
Section: Introductionmentioning
confidence: 99%